The Effect of Self Esteem and Social Support on Muslim Students Academic Integrity - Sabila Rizqiyana; Fitriah M. Suud (Postgraduate Program Magister Pendidikan Agama Islam, 2025)
The issue of academic integrity is a major concern in the world of higher education, especially in a religious-based environment, where violations such as plagiarism and cheating are still rampant. This study aims to examine the influence of self esteem and social support on academic integrity in students. This study uses a quantitative approach with an explanatory survey method, involving 100 active student respondents from various Islamic universities in Yogyakarta. Data collection was carried out through an online questionnaire, and data analysis using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with the help of the SmartPLS application. The results of the analysis showed that self esteem had a positive and significant effect on academic integrity (coefficient = 0.697; p < 0.05), as well as social support (coefficient = 0.290; p < 0.05). The R-Square value of 0.963 indicates that independent variables have a very strong contribution in explaining dependent variables. This study concludes that increasing self-esteem and social support have an important role in shaping academic behavior with integrity in students, especially Muslim students. Self-esteem represents variables from within students plays a more important role than social support variables that represent variables from outside students.